Treatment options for severe pneumonia: focus on pseudomonas pneumonia - Benjamin Margono (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2014)
Pneumonia due to Pseudomonas aeruginosa occurs in several distinct syndromes: 1/ Community Acquired Pneumonia (CAP) usually in patients with chronic lung disease e.g.: COPD / Cystic Fibrosis / bronchiectasis. Rather uncommon : 0.9%-1.9% of patients with CAP requiring hospitalization. 2/ Hospital Acquired Pneumonia (HAP), usually occurring in the ICU after day 4 or VAP. Much more common : 18%. 3/ bacteremic , usually in the neutropenic host e.g. hematologic malignancy, HIV ( Pre HAART : 8-25%; HAART era: 5-6.7%) P.aeruginosa. is a gram negative rod that is ubiquitous in nature and is an opportunistic pathogen in humans. It is a particularly virulent pathogen that produces many virulent factors, including exotoxins, enzymes and biofilms that protects it from host antibodies and phagocytes. Pseudomonas pneumonia carries a notably higher mortality rate than other pneumonia pathogens. Therapy has always been challenging magnified in recent years by the emergence of MDR (multi drug resistant) and PDR ( Pan drug resistant ) pathogen, compounded further by the diagnostic problem of differentiating between colonization and infection, as blood cultures are rarely positive and gram stains have not proven useful. Anti Pseudomonal antibiotics : Aminoglycosides; .β Lactam congeners; Monobactam; Extended spectrum penicillins e,g, piperacillin-tazobactam, Carbapenems; anti pseudomonal fluoroquinoles; Colistin. Combination antibiotic therapy may potentially broaden the antimicrobial spectrum, provide synergistic interaction, decrease emergence of antimicrobial resistance and minimize superinfection. Incombination antibiotic therapy the greatest synergy is obtained by combining an aminoglycoside(A) + antipseudomonal penicillin ( 90%), followed in decreasing order A + cephalosporin ( 80%) then A + carbapenem ( 50%), while the interaction of a fluoroquinolone + A or βlactam is usually indifferent or autonomous. Given the nephrotoxicity of aminoglycosides the following algorithm is proposed : Combination of an anti-pseudomonal penicillin + an aminoglycoside for 3-5 days, then replace the aminoglycoside with an anti-pseudomonal fluoroquinolone for a total of 8-15 days.